1994
DOI: 10.1002/acp.2350080704
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the effects of interviewer training in evaluating the cognitive interview

Abstract: The effectiveness of the cognitive interview (CI) technique has been demonstrated in experimental studies of eyewitness memory conducted in the USA, Germany, and the UK. Much of the research, however, has used college students as interviewers rather than professionals who regularly interview witnesses (e.g. police officers). The aim of this research was to examine the effects of such CI training using experienced police olficers with established interviewing styles. An armed robbery was staged and information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 25 publications
1
85
0
8
Order By: Relevance
“…This facet of study is of considerable importance for, as noted by McMahon (2000), much of the published research investigating the cognitive interview has reported relatively large standard deviations for recall variables (e.g. Aschermann et al, 1991;Koehnken, Schimossek, Aschermann, & Hoefer, 1995;Mantwill, Koehnken, & Aschermann, 1995;McMahon, 2000;Memon, Holley, Milne, Koehnken, & Bull, 1994;. Therefore, while the cognitive interview does seem to be superior to standard questioning of witnesses, the extent of this efficacy appears to be moderated by some other construct that may differ between witnesses.…”
Section: The Present Study: Investigating Visual Imagery In the Cognimentioning
confidence: 84%
“…This facet of study is of considerable importance for, as noted by McMahon (2000), much of the published research investigating the cognitive interview has reported relatively large standard deviations for recall variables (e.g. Aschermann et al, 1991;Koehnken, Schimossek, Aschermann, & Hoefer, 1995;Mantwill, Koehnken, & Aschermann, 1995;McMahon, 2000;Memon, Holley, Milne, Koehnken, & Bull, 1994;. Therefore, while the cognitive interview does seem to be superior to standard questioning of witnesses, the extent of this efficacy appears to be moderated by some other construct that may differ between witnesses.…”
Section: The Present Study: Investigating Visual Imagery In the Cognimentioning
confidence: 84%
“…Although this research was conducted with children, comparisons across studies show that interviewers predominantly use closed question structures irrespective of the age of the witnesses (e.g. Davies, Westscott, & Horan, 2000;Memon, Holley, Milne, Koehnken, & Bull, 1994). The current findings therefore highlight the importance of investing in further research regarding ways to enhance professionals' ability to identify and avoid misleading questions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have compared cognitive interview techniques with hypnosis indicate that performance on them is similar (Geiselman et al, 1985;Kebbell and Wagstaff, 1997). However, unlike hypnosis, the majority of the evidence suggests that, in adults, the cognitive interview does not unduly affect accuracy rates, susceptibility to leading questions, or disrupt confidence accuracy relationships (Geiselman et al, 1985;Geiselman, Fisher, MacKinnon and Holland, 1986;Memon and Bull, 1991;Memon and Kohnken, 1992;Bekerian and Dennett, 1993;Memon, Holley, Milne, Kohnken and Bull, 1994;Geiselman, 1996;. As a consequence, in the UK and USA, the cognitive interview has displaced hypnosis as the preferred mode of memory facilitation in police investigations.…”
Section: Anecdotal Evidencementioning
confidence: 94%